Պաղեստինի հարցը Հուսեյն–ՄակՄահոն նամակագրության մեջ և Լոնդոնի կոնֆերանսում - Զուրաբյան, Լևոն («Զանգակ - 97»)
The article examines the negotiations between the High Commissioner of Great Britain in Egypt and the Sherif of Mecca, especiallv the Palestine question in those negotiations. Düring the World war I the British wanted to gain the Arabs' support against the Türks, promising the Sherif of Mecca to proelaim an independent arab State after the War. Sherif Hussein aecepted their proposa! and. among other Problems, discussed the question of territories. which would be included in the abovementioned State, with Henry MacMahon. the High Commissioner of Great Britain in Egypt. Bascd on the contents of the letters exchangcd between Sherif Hussein and Henry MacMahon from July 1915 to March 1916. one can say that Palestine was intended to be included in the proposed independent arab State, but the British never acccpted that fact. In 1939 the Hussein-MacMahon correspondence was discussed in the London conference, where british and arab delegations made reports on the abovementioned negotiations, the British trying to prove that MacMahon intended to excludc Palestine from the proposed independent arab State and the arabs opposing them.
Keywords: Պատմություն; Քաղաքականություն